PENGARUH BUDAYA ORGANISASI, DISIPLIN DAN MOTIVASI KERJA TERHADAP KINERJA - Afriliansyah Afriliansyah; Dade Suparna; Yumhi Yumhi (E-Journal Studia Manajemen, 2020)
This study aims to obtain information related to whether performance is influenced by organizational culture, discipline and work motivation. Using a causal study through a survey at the Bawaslu District / City Secretariat in Banten Province, Indonesia, for a sample of 40 employees, data for each variable was collected separately by respondents who filled out the questionnaire. The method used in this research is quantitative survey method, while the analysis technique used is path analysis using correlation and regression.The results prove that there is an influence of organizational culture on performance, there is an influence of discipline on performance, there is an influence of work motivation on performance, and there is an influence of organizational culture, discipline and work motivation together on performance.These findings indicate that organizations need to consider the variables of organizational culture, discipline, and work motivation in planning and developing human resources at the Bawaslu District / City Secretariats in Banten Province.